FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEAKTIFAN KADER POSYANDU DI DESA PAHLAWAN SETIA KECEMATAN TARUMAJAYA KABUPATAN BEKASI - Dortea Lewen; Siti Astuti; Emil (Jurnal Nurse, 2020)
The high AKI (Maternal Mortality Rate) and IMR (Infant Mortality Rate) respectively 228/100,000 live births and 34/1,000 live births in Indonesia encourage several health services, especially posyandu services and puskesmas to be active in carrying out activities that reduce the MMR and IMR values. Posyandu is a service in the working area of ​​the Puskesmas. The existence of Posyandu is driven by the activeness of Posyandu cadres in optimizing their participation in improving health efforts in Indonesia. Cadres in the implementation of posyandu are the central point of activities in posyandu. Its participation and activity is expected to be able to mobilize community participation. The activity of cadres in Pahlawan Setia Village still does not meet the minimum requirements, where 9.8% of cadres do not carry out posyandu activities for various reasons. This study aims to determine the factors associated with the level of activeness of cadres in the implementation of posyandu activities. The factors are age, level of education, level of knowledge, years of being a cadre, history of coaching and training, and family support. The statistical test of this study was chi-square and used a total sampling of 58 respondents. The results of this study indicate that there is a relationship between age and the activity of posyandu cadres (p-value = 0.023); there is a relationship between the education level of cadres and the activeness of posyandu cadres (p-value = 0.000); there is a relationship between the knowledge level of cadres and the activeness of posyandu cadres (p-value = 0.000); there is a relationship between the length of time being a cadre and the activity of posyandu cadres (p-value = 0.000); there is a relationship between the history of coaching and training of cadres with the activeness of posyandu cadres (p-value = 0.000); and there is a relationship between family support and the activity of posyandu cadres (p-value = 0.000). The results of this study can provide suggestions and input to posyandu services where the factors related to the activity of cadres.